CONCENTRATION OF PASSENGER TRAFFICS and THE FREIGHT traffics AT THE RUSSIAN AIRPORT - T. Bogdanova; N. Subbotin (Вестник университета, 2017)
Results of a research of concentration the freight transport market at the Russian airport are presented in this article. Calculations of indexes of concentration, coefficients of concentration of Herfindahl-Hirschman both on departure of passengers in general, and on separate types of transport (in the internal message, the international message) and on a cargo transportation are executed. The carried-out calculations allowed to estimate concentration on separate segments of the market of air transport. The executed research will form a basis for development of development strategies of the regional Russian airports.